Is there a unique integration mechanism of Agrobacterium T‐DNA into a plant genome?. Issue 5 (3rd February 2021) - Faure, Denis
Abstract : This article is a Commentary on Nishizawa‐Yokoi et al. (2021), 229 : 2859–2872 .